Assessment of radium and supported radon in ground water from Cameron Highlands area / Nor Shazlina Zainal - Zainal, Nor Shazlina (2014)
Radon chamber using SSNTD CR39 (Columbian Resin #39) was developed and optimized to measure supported 222Rn activity concentration through degassing process in ground water samples from Cameron Highlands, Malaysia. This ground waters contained natural radioactivity associated with uranium and thorium that present in rocks and soils. If this water is inhaled or ingested by human, they may be exposed to the emission of energetic alpha particle from radium and supported 222Rn decaying process in this water. The measurement of supported 222Rn activity concentration in ground water sources, rivers, treatment plants and its distribution areas samples was successftilly carried out using CR39 inside radon chamber. Supported Rn in samples ranged from 0.22±0.13 to 1.45±0.09 Bq/L. Validation of radon chamber using CR39 with continuous radon monitor has demonstrated this analytical technique was able to produce reliable analytical result for measuring supported222 Rn in water. The supported 222Rn results from radon chamber method have been verified with 222Ra activity concentration results using gamma spectrometry technique through its progenies which a technique for measuring supported radon in water. Supported 222Rn in samples from selected sites was lower than 11 Bq/L, the limit of radon in drinking water (USEPA 1999). The annual ingested dose for supported 222Rn consumption was calculated based on consuming 2L of water/day and found to range from 45±6 to 287±27 ^iSv/yr which was below than 290 |iSv/yr (worldwide average annual effective dose). This is due to the low levels of supported 222Rn that indicates all investigated samples are acceptable for consumption.